Elucidating the role of long intergenic non-coding RNA 339 in human endometrium and endometriosis. (8th February 2021) - Holdsworth-Carson, Sarah J; Churchill, Molly; Donoghue, Jacqueline F; Mortlock, Sally; Fung, Jenny N; Sloggett, Clare; Chung, Jessica; Cann, Leonie; Teh, Wan Tinn; Campbell, Katie-Rose; Luwor, Rodney; Healey, Martin; et al.
ABSTRACT: Endometriosis is a complex disease, influenced by genetic factors. Genetic markers associated with endometriosis exist at chromosome 1p36.12 and lead to altered expression of the long intergenic non-coding RNA 339 (LINC00339), however, the role of LINC00339 in endometriosis pathophysiology remains unknown. The aim of this work was to characterize the expression patterns of LINC00339 mRNA in endometrium and endometriotic lesions in situ and to determine the functional role of LINC00339 in human endometrium. We employed RNA-sequencing (RNA-seq), quantitative RT-PCR and in situ hybridization to investigate the abundance of LINC00339 transcripts in endometrium and endometrial cell lines and to describe the pattern and localization of LINC00339 expression in endometrium and endometriotic lesions. LINC00339 mRNA expression was manipulated (overexpressed and silenced) in endometrial stromal cell lines and RNA-seq data from overexpression models were analysed using online bioinformatics platforms (STRING and Ingenuity Pathway Analysis) to determine functional processes. We demonstrated the expression of LINC00339 in endometriotic lesions for the first time; we found LINC00339 expression was restricted to the lesion foci and absent in surrounding non-lesion tissue. Furthermore, manipulation of LINC00339 expression in endometrial stromal cell lines significantly impacted the expression of genes involved in immune defence pathways. These studies identify a novel mechanism for LINC00339 activity in endometrium and endometriosis, paving the way for future work, which is essential for understanding the pathogenesis of endometriosis.